2017
DOI: 10.1007/s10570-017-1217-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemically imaging the interaction of acetylated nanocrystalline cellulose (NCC) with a polylactic acid (PLA) polymer matrix

Abstract: The non-covalent interaction of acetylated nanocrystalline cellulose (AC-NCC) with polylactic acid (PLA) in a composite blend has been studied at the micron scale by synchrotron Fourier Transform Infrared (FTIR) microspectroscopy. Microtomed sections of AC-NCC in PLA showed strong, localized carbonyl stretching (νC=O) absorbance characteristic of the cellulose acetylation, and this was observed on the surface of larger aggregated AC-NCC particles. A shift in the νC=O IR absorption peak of AC-NCC in PLA, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 35 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…In contrast, at 140 • C, greater PLA viscosity reduces flow and ingress into the wood matrix and was associated with the retention of a thicker bondline. In assessing the tensile strength of bondlines, the relative thickness of the PLA matrix may impact the stress transfer across PLA bondlines, particularly given that PLA is a hard, rigid polymer below its glass transition when tested [17,18]. However, with tensile testing, a thinner PLA bond appeared able to transfer stress and, in combination with greater interfacial adhesion and mechanical interlocking, provided higher performance of composites formed at 200 • C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, at 140 • C, greater PLA viscosity reduces flow and ingress into the wood matrix and was associated with the retention of a thicker bondline. In assessing the tensile strength of bondlines, the relative thickness of the PLA matrix may impact the stress transfer across PLA bondlines, particularly given that PLA is a hard, rigid polymer below its glass transition when tested [17,18]. However, with tensile testing, a thinner PLA bond appeared able to transfer stress and, in combination with greater interfacial adhesion and mechanical interlocking, provided higher performance of composites formed at 200 • C.…”
Section: Discussionmentioning
confidence: 99%
“…However, as above, wood fibre inclusion with PLA did not significantly impact spruce composite performance. Furthermore, polymer crystallinity around wood-polymer interfaces and within the plastic/polymer matrix will also impact performance, so must also be considered in the context of interfacial properties [6,17,18]. In related adhesion studies, nano-and molecular-scale interactions have also been found to be important [14], and these will also need to be considered in sandwich composite formation and performance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, there has been an increase in the use of imaging methodologies to study composite materials containing cellulose as a ller. [27][28][29] These studies have focused on the distribution of CNCs in a polypropylene matrix composite, 27 the intermolecular interaction between acetylated nanocrystalline cellulose (AC-NNC) and polylactic acid (PLA) 28 and the dispersion efficiency of additives. 29 In the present study, Raman imaging combined with chemical images are used to quantify the distribution of CNCs in high-density polyethylene (HDPE) composites.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to evaluate the amount of carvacrol entrapped in the films, the spectral region 830-800 cm −1 of the spectra is provided in the panel b of the same figure [23,25]. Note that the spectra were normalized to the intensity of the peak centered at 753 cm −1 , belonging to "fingerprint" region of PLA-phase of BF [23][24][25]31]. The results highlighted that carvacrol signal in BF-D-C has an intensity almost threefold that of BF-C.…”
Section: Characterization Techniquesmentioning
confidence: 99%